Adaptation of the EFL methods course in the classroom : a case study / Nafiseh Salehi - Salehi, Nafiseh (2011)
The present study is aimed at exploring high school English teachers’ conceptions and experiences about the contribution of the EFL methods course in providing teachers with the knowledge and skills of various language teaching methods. It also examines how the teachers use or adapt the methods courses in their practice. This qualitative study was guided by three research questions: 1. What were the main characteristics of the EFL methods course in the preservice EFL teacher education program in Iran?; 2. How did the EFL methods course contribute to the practices of high school English teachers in Semnan Province?; and 3. How do high school English teachers in Semnan province, Iran use or adapt the language teaching methods in their classrooms? The data sources comprised of individual interviews with eight high school EFL teachers and three EFL methods course lecturers as well as observations and analysis of the relevant EFL documents. The research site comprised of Semnan, Shahroud, Damghan and Garmsar counties of the Semnan Province in Iran. The data was analyzed through the lens of sociocultural theory of situated learning. The findings of the study revealed that the eight high school English teachers were taught all the language teaching methods presented in the reference books for the EFL methods course offered by their lecturers. However, a majority of the participants mentioned that these methods had not been contextualized in their EFL methods course, and hardly any link had been made between theory and practice. The majority of the participants believed that participating in the EFL methods course has mostly helped them develop their content knowledge in the field of ELT. They maintained that they had been passive receivers of information and their EFL methods course was mostly theory-loaded, and lecture-centered. They referred to the social interactions with their fellow student teachers as a source of learning. They asked for audio-visual aids in the EFL methods course classes. The same issues were raised by the three EFL methods course lecturers as well, such as the decontextualization of theory and practice, loading the students with theoretical knowledge and managing the EFL methods classes through lecturing because of the institutional constraints. In describing their teaching methodologies, six high school EFL teachers mentioned that they were eclectic in selecting their teaching methods. One of the teachers identified her methodology as within the paradigm of Communicative Language Teaching Approach (CLT) and the other asserted that his method was imposed by the textbooks. Despite these claims, the observation data showed that the dominant approach was the Grammar Translation. The study concluded by addressing key implications for the policy makers, decision makers and other key stakeholders in preservice EFL teacher education programs in Iran.